The Success of Governor Anies Rasyid Baswedan's Leadership in Leading DKI Jakarta from 2017-2022 - Muksin, Ahmad; Amsori; Rofik, Rosadi; Karim, Muqaddim; Aryanto; Arizal (JOELS: Journal of Election and Leadership, 2024)
This research aims to explore and analyze Governor Anis Rasyid Baswedan's successful leadership of Jakarta, Indonesia. Using qualitative research methods and a literature review approach, this study conducted an in-depth analysis of various literature, performance reports, and news stories related to Governor Anis Rasyid Baswedan's leadership. The main focus of the research was to identify the key factors that contributed to the success of his leadership in overcoming challenges and achieving development goals at the local level. The results of this study are expected to provide a deeper understanding of the leadership strategies and styles used by Governor Anis Rasyid Baswedan that have contributed to his successful leadership of Jakarta. The implications of this research are expected to provide constructive insights for the development of regional leadership in Indonesia